Cognitive trio: relationship with major depression and clinical predictors in Han Chinese women. Issue 11 (November 2013) - Wang, L.; Liu, L.; Shi, S.; Gao, J.; Liu, Y.; Li, Y.; Zhang, Z.; Wang, G.; Zhang, K.; Tao, M.; Gao, C.; Li, K.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Previous studies support Beck's cognitive model of vulnerability to depression. However, the relationship between his cognitive triad and other clinical features and risk factors among those with major depression (MD) has rarely been systematically studied. Method The three key cognitive symptoms of worthlessness, hopelessness and helplessness were assessed during their lifetime worst episode in 1970 Han Chinese women with recurrent MD. Diagnostic and other risk factor information was assessed at personal interview. Odds ratios (ORs) were calculated by logistic regression. Results Compared to patients who did not endorse the cognitive trio, those who did had a greater number of DSM-IV A criteria, more individual depressive symptoms, an earlier age at onset, a greater number of episodes, and were more likely to meet diagnostic criteria for melancholia, postnatal depression, dysthymia and anxiety disorders. Hopelessness was highly related to all the suicidal symptomatology, with ORs ranging from 5.92 to 6.51. Neuroticism, stressful life events (SLEs) and a protective parental rearing style were associated with these cognitive symptoms. Conclusions During the worst episode of MD in Han Chinese women, the endorsement of the cognitive trio was associated with a worse course of depression and an increased risk of suicide. Individuals with high levels of neuroticism, many SLEs and high parental protectiveness were at increased risk for these cognitive depressive symptoms. As in Western populations, symptoms of the cognitive trio appear to play a central role in the psychopathology of MD in Chinese women.